Sustainable Development and International Law: The Way Forward - Working Group on Environmental Law (European University Institute, 2007)
This Working Paper collects the contributions that were elaborated for a Roundtable held at the European University Institute in May 2006. The Roundtable was meant to discuss the emergence of the new field of studies in law: Sustainable Development Law. The Roundtable gathered members of the Working Group on Environmental Law of the EUI and guest speakers from European Universities. Together, professors and researchers try to delineate the material content of such new field of law, its relation with the more familiar field of environmental law, and underlined some problems arising from the legal use of concepts such as sustainable development, sustainable management and sustainability